Domiciliary Treatment of Severe Acute Malnutrition - , BhoyeR; , PhadkeM; , AguayoV; , IraniS; , NairR; , PawarS; , PatelT; , GaneshA; , KhoslaJ; , SaunikS (International Journal of Nutrition, 2017)
Background Severe acute malnutrition (SAM) is rampant in the children of hilly and inaccessible tribal region of Nandurbar, Maharashtra in India. It is estimated that nearly 5% of the children under five years have SAM. Objectives To assess the therapeutic efficacy of 3 types of nutrition protocols administered largely at home in SAM children from Nandurbar, Maharashtra. Methodology This study is a part of a larger three arm open label trial using 3 therapeutic feeds i.e. C-RUTF (Centrally produced ready to use therapeutic food), L-RUTF (locally prepared ready to use therapeutic food) and ARF (locally prepared amylase rich food) in children of SAM who attended the health facility and completed the treatment protocols for 8 weeks (All ‘per protocol patients’) and were between 1 to 3 years of age. The larger study included children aged 6 months to 59 months who were given same therapeutic feeding protocol. Findings A total of 450 SAM babies between 12-36 months. attended the outpatient therapeutic program during the period of July 2014 to December 2015 and completed the given protocol of therapeutic feeding program. 242(53.7%) were males and 208(46.2%) females. Out of these, 150 received C-RUTF, 150 received L-RUTF and 150 received ARF. Out of C-RUTF group 83(55.3%) recovered, in L-RUTF 70(46.7%) recovered and from ARF group 69(46.0%) recovered. The difference was statistically significant.(p=0.03) Total recovery rate was 49.3% in comparison to another under publication study by our group on 3418 children aged 6 months to 59 months, where recovery was 36.8%. Average weight gain per day was 3.54 ± 2.36 g/kg/day, 2.61 ± 2.12 g/kg/day, 2.60 ± 1.50 g/kg/day in the 3 arms respectively. Conclusion This study proves that domiciliary treatment with 3 types of therapeutic feeds gives recovery rate of 49.3%, there by meaning that SAM Children without complications can be treated at home with visit to health facility once a week. Of all the therapeutic feeding protocols C-RUTF had best recovery rates (55.3%) compared to others, the difference being statistically significant. Average weight gain per kg per day inC-RUTF group was 35.8 % higher than the other 2 groups.
Keywords: Severe Acute Malnutrition; Therapeutic Feeding; Ready To Use Therapeutic Food; Nutrition; Children